Spring coccolithophore production and dispersion in the temperate eastern North Atlantic Ocean - Schiebel, Ralf; Brupbacher, Ursula; Schmidtko, Sunke; Nausch, Günther; Waniek, Joanna J.; Thierstein, Hans-R. (Journal of Geophysical Research, 2011)
ISSN:0148-0227 ISSN:2169-9275